2021
DOI: 10.18632/aging.202888
|View full text |Cite
|
Sign up to set email alerts
|

Genetic landscape of breast cancer and mutation tracking with circulating tumor DNA in Chinese women

Abstract: Considerable efforts have been devoted to exploring the breast cancer mutational landscape to understand its genetic complexity. However, no studies have yet comprehensively elucidated the molecular characterization of breast tumors in Chinese women. This study aimed to determine the potential clinical utility of peripheral blood assessment for circulating tumor-derived DNA (ctDNA) and comprehensively characterize the female Chinese population’s genetic mutational spectrum. We used Omi-Seq to create cancer pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 50 publications
4
6
0
Order By: Relevance
“…In addition, we profiled drug responserelated genomic variants, evaluated the prognostic value of the ctDNA fraction and bTMB, and assessed the ability of ctDNA to monitor disease progression. In this study, molecular profiling of ABC revealed genomic variants consistent with several previous reports, and TP53 (44.0%) and PIK3CA (28.4%) were the two most commonly altered genes [2,35,38,41,42]. TP53 is a well-characterized tumour suppressor gene that acts as a regulator of key cellular processes involved in controlling cell proliferation and maintaining genomic stability [43,44].…”
Section: Discussionsupporting
confidence: 89%
“…In addition, we profiled drug responserelated genomic variants, evaluated the prognostic value of the ctDNA fraction and bTMB, and assessed the ability of ctDNA to monitor disease progression. In this study, molecular profiling of ABC revealed genomic variants consistent with several previous reports, and TP53 (44.0%) and PIK3CA (28.4%) were the two most commonly altered genes [2,35,38,41,42]. TP53 is a well-characterized tumour suppressor gene that acts as a regulator of key cellular processes involved in controlling cell proliferation and maintaining genomic stability [43,44].…”
Section: Discussionsupporting
confidence: 89%
“…(E) When HR+ groups were stratified by clinicopathological features that increase risk of relapse, the detection rate was significantly lower in the low-risk than the high-risk group of HR+ HER2À. The HRÀ HER2À group showed the highest number of mutations per patient, consistent with the literature that triple-negative breast cancer had higher tumor mutational burden than other subtypes [21,22], making it a good candidate for immune checkpoint therapy.…”
Section: Discussionsupporting
confidence: 82%
“…Our data showed that 94.8% of the Vietnamese patients had at least one somatic mutation in the 95 cancer‐associated genes. The HR− HER2− group showed the highest number of mutations per patient, consistent with the literature that triple‐negative breast cancer had higher tumor mutational burden than other subtypes [ 21 , 22 ], making it a good candidate for immune checkpoint therapy.…”
Section: Discussionmentioning
confidence: 87%
“…Along with cells, isolated nucleic acids have also been studied for their potential role as cancer biomarkers. Several studies have evaluated circulating DNA as a predictor of treatment response, disease progression [ 94 ], shorter PFS [ 95 , 96 ], and worse patient outcomes [ 97 , 98 ]. In addition, four studies evaluated mutations and/or gene expression in ctDNA.…”
Section: Prediction Of Treatment Response and Early Detection Of Relapsementioning
confidence: 99%